The Reform of Italian Cooperative Banks : Discussion of Proposals - Gutierrez, Eva (IMF Working Papers; Working Paper ;, 2008)
This paper argues that the governance framework of cooperative banks may hamper raising capital, particularly at time of distress, complicating the bank resolution process ?specially for large banks?and may not provide adequate incentives to control banks' management. Reforms should preserve the positive characteristics that make cooperative banks a valuable addition to the Italian financial system, while providing enough flexibility and incentives for banks to adopt a suitable governance model. Our empirical analysis suggests that cooperative banks may enjoy a higher degree of monopoly power than commercial banks. Thus, regulations and the enforcement of antitrust policies should ensure a leveled playing field.